The Effect of Collaborative Strategy Reading and Guided Reading Peer Questioning Strategy on Students’ Achievement in Reading Comprehension - Theoria Indah Swari Sinaga; Erika Sinambela; Agustinus Gea; Carolina (Jayapangus Press, 2020)
The purpose of this study was to describe the influence of students in determining collaborative reading strategies and integrated reading questions and answers from class VIII SMP Swasta Nusantara Lubuk Pakam. This research was conducted using Two-Way ANOVA. The research subjects were students of class VIII of Lubuk Pakam Nusantara Private Junior High School which consisted of 30 students. The instrument used to collect data is multiple choice. The population is 30 students. The results of this study, obtained using ANOVA analysis, the comparison of Fcount and Ftable at a significant level is the learning strategy used by Nusantara Private Junior High School Lubuk Pakam Fcount p = 0.320> 0.05 or Fcount = 1.154 < Ftable = 3.10, not significant.